Mitigasi Bencana Longsor dengan Penanaman Pohon di Kawasan Rawan Desa Basseang - jusmawandi; Rahman, Rahman; Muhlisah, Nurul (Jurnal Inovasi dan Pengabdian Kaa Mieera, 2024)
Basseang Village, Pinrang Regency is an area with a hilly contour that is prone to landslides, especially during high rainfall. The lack of vegetation as a soil retainer is the main factor that increases the risk of disasters in this area. In addition, there is a diversification of cocoa plantation crops to corn which is considered to have better economic benefits. From this change in plant types, it has an impact on the strength of the soil that is prone to landslides. This study aims to implement landslide disaster mitigation through tree planting with a community-based approach. The method used is Participatory Action Research (PAR), which involves the community in every stage, from planning, seed distribution, to planting and maintenance. A total of 950 tree seedlings, consisting of candlenut, coffee, and cocoa, were distributed to 20 heads of families in landslide-prone areas. The results of the program show that this activity not only improves soil stability, but also builds public awareness of the importance of environmental conservation. In addition, the formation of environmental care groups is an indicator of the sustainability of the program. In conclusion, the participatory approach to disaster mitigation in Basseang Village has proven effective in reducing the risk of landslides and providing economic benefits to the local community.